Funding the future: Financial aid’s role in postgraduate choices and success - Yu, D.; Pather, S.; Beukes, R.; Swanepoel, C.; Arendse, R. (South African Journal of Higher Education, 2026)
Background: Ensuring a pipe-line of students from undergraduate into postgraduate phase of higher education is of critical importance to most countries’ post-school strategies and economic growth. While there are some insights in the international literature on the role of funding in respect of postgraduate access and success, there are limited studies in the South African context. This study examined the impact of prospective financial aid receipt on students registered at a selected South African university. Method 1: The study first analysed the financial aid receipt status and academic performance of postgraduate students on a selected sample of Commerce students of a South African university in 2019 (the last ‘normal’ year before COVID-19 took place). The data indicates that 46 per cent of these students received financial aid. The recipients were predominantly African female full-time students. Findings 1: The empirical findings indicated that financial aid receipt was associated with a significant shorter studies completion time at Postgraduate Diploma (PGDip) level, followed by Honours level. Method 2: The study proceeded to use primary data collected from the 2023 final-year undergraduate students, as well as those in Year 1 (Honours and PGDip), and Year 2 (Masters) students of the same university on their intention to pursue the next level of postgraduate studies in 2024. A total of 159 responses were received and the results showed that 88 per cent of final-year undergraduate students; 64 per cent of first-year postgraduate students; and 45 per cent of Masters students had an intention to proceed into further postgraduate studies. Findings 2: The primary reason for not intending to pursue further studies (Masters and Doctorate) was the need to become economically active through work opportunities to provide financial support to their families. In respect of final-year undergraduate students there were two factors that would influence their decision to apply for postgraduate studies, namely meeting minimum entry requirements and receipt of financial aid. Significance of research: This research is important as it provides valuable insights on the key factors that drive the students’ decision to pursue further postgraduate studies and the role of financial aid to improve students’ academic success at postgraduate level.